Приключения Тома Сойера - Твен Марк (Приключения и фантастика, 2004)
Экземпляры: Д. О. (20210503) / Инвентарный номер: 48382 / Цена: 96.00 / Сис.шифр: И(Амер) / Авт.знак: Т 26 / ГРНТИ: 17.82 / ББК: 84(7Сое)